The acute and temporary modulation of PERIOD genes by hydrocortisone in healthy subjects. (20th October 2016) - Yurtsever, Türkan; Schilling, Thomas M.; Kölsch, Monika; Turner, Jonathan D.; Meyer, Jobst; Schächinger, Hartmut; Schote, Andrea B.
ABSTRACT: The physiological stress system and the circadian clock system communicate with each other at different signaling levels. The steroid hormone cortisol, the end-effector of the hypothalamus–pituitary–adrenal axis, is released in response to stress and acts as a mediator in circadian rhythms. We determined the effect of escalating cortisol doses on the expression of PERIOD genes ( PER1, PER2 and PER3 ) in healthy subjects and analyzed whether the glucocorticoid receptor (GR) is involved in the cortisol-mediated PERIOD gene expression. Forty participants (50% males and 50% females) were randomly assigned to groups receiving a saline placebo solution or 3 mg, 6 mg, 12 mg and 24 mg of hydrocortisone. Blood was drawn every 15 min to measure quantitative gene expression of PER1, PER2 and PER3 . A potential role of the GR was determined by an ex vivo study stimulating whole blood with hydrocortisone and RU486 (a GR antagonist). As a result, moderate doses of hydrocortisone produced an acute and temporary induction of PER1 and PER3 mRNA levels, whereas PER2 was not responsive to the hormone administration. The cortisol-dependent induction of PER1 was blocked by the GR antagonist in whole blood after treatment with hydrocortisone and RU486 ex vivo . In conclusion, acute pharmacological stress modulated the expression of PER1 and PER3 in whole blood temporarily in our short-term sampling design, suggesting that these circadian genes mediate stable molecular mechanisms in the periphery.